The PERK/ATF4 pathway is required for metabolic reprogramming and progressive lung fibrosis - Pandey, Jyotsana; Larson-Casey, Jennifer L.; Patil, Mallikarjun H.; He, Chao; Pinthong, Nisarat; Carter, A. Brent (JCI insight, 2025)
Asbestosis is a prototypical type of fibrosis that is progressive and does not resolve. ER stress is increased in multiple cell types that contribute to fibrosis; however, the mechanism(s) by which ER stress in lung macrophages contributes to fibrosis is poorly understood. Here, we show that ER stress resulted in protein kinase RNA-like ER kinase (PERK; Eif2ak3) activation in humans with asbestosis. Similar results were seen in asbestos-injured mice. Mice harboring a conditional deletion of Eif2ak3 were protected from fibrosis. Lung macrophages from asbestosis individuals had evidence of metabolic reprogramming to fatty acid oxidation (FAO). Eif2ak3fl/fl mice had increased oxygen consumption rate (OCR), whereas OCR in Eif2ak3-/- Lyz2-cre mice was reduced to control levels. PERK increased activating transcription factor 4 (Atf4) expression, and ATF4 bound to the Ppargc1a promoter to increase its expression. GSK2656157, a PERK-specific inhibitor, reduced FAO, Ppargc1a, and Aft4 in lung macrophages and reversed established fibrosis in mice. These observations suggest that PERK is a therapeutic target to reverse established fibrosis.